The role of spiral Computerized Tomography in diagnosis of stroke - mohammed, Eman (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The aim of this study is to determine the role of spiral Computerized Tomography in the diagnosis and detection the types of stroke. Methodology: One hundred sixty two patients (162) (99 males and 63 females) their ages ranging from (13 – 80) year, all of them are suffering from stroke. They were collected randomly from spiral Computerized Tomography unit in Baquba Teaching hospital during the period from November / 2010 to December / 2011 .All the patients were examined clinically and then done spiral Computerized Tomography examination. Results : The results of this study showed that the stroke effected different age groups and both sex but males is more affected than the females .The results of spiral Computerized Tomography examination were 97 patient ( 59.9 % ) have ischemic stroke and 65 patient ( 40.1 % ) have hemorrhage stroke . Recommendation: The study recommended that great focusing to do the examination by spiral computerized tomography if the patients have no contraindications for during examined with it because it has high accuracy and efficiency in diagnosis of the stroke, also recommended to do an educational programs to improve awareness of society about the risk factors and early clinical features to help of early diagnosis and management of stroke.